“Tell Me a Story in Sign Language”: An Approach to the Process of Reading, Translating and Interpret in Mexican Sign Language - Cruz-Aldrete, Miroslava (2024)
This paper discusses how narratives in Mexican Sign Language (LSM) have become relevant in two ways: the first is related to the acquisition and development of LSM at early ages; the second responds to the use of picture books as a strategy to bring Deaf children closer to written Spanish, which has given rise to the interpretation and translation of literary works aimed at children; in turn, this demands the adaptation of these texts in order to offer them appropriately to their recipients. This is ongoing research that is part of a research project in which the acquisition of SLM as a first and second language is studied from the perspective of the bilingual/intercultural educational model offered to Deaf students in Mexico. From the analysis of the narratives in LSM that are offered to Deaf children to strengthen their competence in sign language and their literacy in a second language, we recognize the importance of discussing the role of cultural and linguistic mediation of teachers and interpreters, deaf and hearing, for the achievement of these objectives.